The Influence of Price Dimensions and Product Quality on Purchase Decisions Mediated by E-Word of Mouth in ihe Tiktok Application - Prasetyo Harisandi; Purwanto Purwanto (President University, 2022)
Internet use in Indonesia is dominated by the use of social media, this is what makes e-marketing grow where marketing practices through social media are used as a product marketing tool to promote company brands. One of them is Tiktok, which is used to make online/live sales, which is currently chosen by industry players. e-word of mouth (E-WOM) has become a growing phenomenon along with the increasing use of social networking sites. This study aims to test and obtain empirical evidence of the effect of price, product quality on e-word of mouth, e-word of mouth on purchasing decisions and the effect of price on purchasing decisions mediated by e-word to mouth and the effect of product quality on purchasing decisions mediated by e-word of mouth in the TikTok application. The population in this study are all users who have shopped through the Tiktok application, the number of which is unknown or infinite, the number of samples is determined by the Roscoe method so that a sample of 100 people is taken, and the samples are taken using a random sampling technique. The analysis tool used is path analysis using Partial Least Square (PLS). The results of this study indicate that price has a positive effect on e-word of mouth, product quality has a positive effect on e-word of mouth, e-word to mouth has a positive effect on purchasing decisions, price has a positive effect on purchasing decisions mediated by e-word to mputh and product quality also have a positive effect on purchasing decisions mediated by e-word of mouth.